Arquitectura e Personalização. O impacto das tecnologias CAD/CAM - Manuel António de Carvalho Oliveira (2014)
Today, the use of digital design and fabrication technologies is challenging the architectural practice at many levels. Its most visible impacts seems to be related with expanding the geometric and constructive possibilities in the design and allowing the exploration of non-standard modes of production. In this context, digital technologies are promoting a new degree of customization that can affect the way architects think and build their designs. The present thesis looks to investigate this condition in order to uncover its potentials and limitations. It starts by framing the different modes of production that have ruled the history of architecture, and surveying the state of the art of digital technologies that support new conditions for customization in architecture. In order to evaluate such opportunity, a critical analysis of the subject is conducted. Based in examples from contemporary architecture (eg. works by Frank Gehry, Zaha Hadid, UN Studio, etc.), it discusses the emerging customization possibilities at three levels: the form, the structure and the building component. To complement this study, the author presents three works from his own experience developed in both the academic and research contexts. The overall conclusion of this investigation tends to realize that technologically, architects face nowadays an endless world of design and constructive strategies to engage with full customization. However, considering the old constraints that still define the practice of architecture (eg. economy or building logistics) architects tend in most of the cases to negotiate the implementation of the digital possibilities with more traditional approaches to design and construction. The present thesis thus aims to illustrate this spectrum of variation in the discipline in the current digital era.